West African Economic and Monetary Union : Staff Report On Common Policies for Member Countries-Press Release; Staff Report; and Statement by the Executive for the WAEMU. (IMF Staff Country Reports; Country Report ;, 2022)
The WAEMU has, so far, demonstrated strong resilience to the Covid crisis. The economic rebound that started in the second half of 2020 firmed up in 2021, while fiscal and monetary policies remained supportive. External reserves have risen to comfortable levels and the financial system appears to be broadly sound. However, the region faces significant challenges to ensure the sustainability of macroeconomic policies, while supporting the economic recovery and navigating the uncertain outlook.